2013
DOI: 10.1177/0145482x1310700607
|View full text |Cite
|
Sign up to set email alerts
|

Disability Insurance Beneficiaries with Visual Impairments in Vocational Rehabilitation: Socio-demographic Influences on Employment

Abstract: Introduction Given mutual concerns of vocational rehabilitation and the Social Security Administration, our purpose was to evaluate the effect of current individual and economic factors on competitive employment for Social Security Disability Insurance (SSDI) beneficiaries with visual impairments in vocational rehabilitation. Methods Using fiscal year 2010 RSA-911 data on 4,478 SSDI beneficiaries whose vocational rehabilitation services had concluded, we conducted descriptive and multilevel analyses to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 11 publications
5
47
1
2
Order By: Relevance
“…1 Several previous studies have demonstrated it is unlikely that visually impaired individuals are employed. [2][3][4][5][6][7][8][9] However, the estimates for workforce participation presented in these studies were subject to bias because data were not population based, 3,5,6 relied on self-reported visual impairment (as opposed to measured visual acuity), 2,4,5 did not adhere to a clearly defined definition of visual impairment, 3,5 and/or analyzed individuals receiving vocational services. 6,8,9 Here, we assess employment rates by vision status in a nationally representative sample of working-age American individuals analyzed as part of the National Health and Nutrition Examination Survey.…”
mentioning
confidence: 99%
“…1 Several previous studies have demonstrated it is unlikely that visually impaired individuals are employed. [2][3][4][5][6][7][8][9] However, the estimates for workforce participation presented in these studies were subject to bias because data were not population based, 3,5,6 relied on self-reported visual impairment (as opposed to measured visual acuity), 2,4,5 did not adhere to a clearly defined definition of visual impairment, 3,5 and/or analyzed individuals receiving vocational services. 6,8,9 Here, we assess employment rates by vision status in a nationally representative sample of working-age American individuals analyzed as part of the National Health and Nutrition Examination Survey.…”
mentioning
confidence: 99%
“…Empirical results on the effects of gender are consistent, demonstrating that males exhibit better return-to-work outcomes than females, everything else being equal (Cancelliere et al, 2016;Cornelius, Van Der Klink, Groothoff, & Brouwer, 2011;Feuerstein, Berkowitz, Haufler, Lopez, & Huang, 2001;Giesen J. & Cavenaugh Brenda, 2013;Saltychev, Tenovuo, & Laimi, 2013;Stergiou-Kita, Mansfield, & Sokoloff, 2016).…”
Section: Research Questionsmentioning
confidence: 85%
“…The level of prior education has also been found to be strongly correlated with return-to-work outcomes (Blackwell et al, 2004;Cancelliere et al, 2016;Giesen J. & Cavenaugh Brenda, 2013); the likelihood of successfully returning to work increases with additional education.…”
Section: Chapter 6: Conclusion and Policy Implicationsmentioning
confidence: 99%
See 2 more Smart Citations